ANALISIS KEKUATAN HUKUM ATAS PENGAMBILAN KEPUTUSAN DENGAN METODE CIRCULAR RESOLUTION PADA PERSEROAN TERBATAS - Slivia Cendana; Eva Fortuna; Devina Trianti; Andryawan Andryawan (Fakultas Hukum Universitas Tarumanagara, 2021)
One of the aims and objectives of the Limited Liability Company is to make decisions for the sustainability of the Company. This decision making is carried out by shareholders in the organs of a limited liability company, namely the General Meeting of Shareholders (GMS), generally this decision making is carried out in a meeting that has been previously scheduled as stated in the Articles of Association of a Limited Liability Company. However, there are other ways of decision making in Limited Liability Companies which are carried out by shareholders besides the GMS as regulated in Law Number 40 of 2007 Article 91 concerning Limited Liability Companies, which are known as circular resolutions. This Circular Resolution is a mechanism provided by law for the convenience of shareholders. This study aims to determine the legal power of decision making and to determine the effectiveness of decision making by using the circular resolution method in Limited Liability Companies. This research method is normative research by examining the positive rule of law in Indonesia and literature studies. The results of this study indicate that decisions made by Circular Resolution have binding legal force as well as decisions made by the GMS by calling beforehand. This Circular Resolution can be carried out as a substitute for the conventional GMS as stated in the Articles of Association of the Company. The circular resolution does not have to mandatorily written on the notarial deed to prove its legal legitimacy, but there are provisions regarding several decisions that must be stated on the notarial deed. Circular resolution decisions are effective because these decisions are generally made to the convenienxe of limited liability companies which are closed, which the closed limited liability company only consists of a few shareholders so obtaining a signature as a form of validity of the decision is easier compared to publicly listed companies.